Transfer Passenger Process at Keflavík International Airport - Þórdís Anna Björnsdóttir 1993- (2019)
Keflavík International airport aims to serve as a transfer airport cross the North Atlantic between Europe and America, as the airport’s offers quick transfer times. Due to these quick transfer times at KEF the on-time performance at KEF is affected. In this research the methodology of business process management was used. Business process management involves identifying current issues in the process, managing chains of event, activities and decisions that increase business and customer value. Business process management’s purpose is to improve overall quality in the process, of a product and service. The aim of this research is to improve the current transfer passenger process at KEF by using the methodology of business process management. The current status of transfer passenger process at KEF was observed and analyzed and suggestions for improvements were presented. Few of the suggestions for improvements were then implemented and the performance measured used in this research before and after implementation was the total transfer passenger time at KEF from arrival to departure. The majority of issues in the current process could be linked to methods performed by the airport or airlines as well as material, mainly the airport facilities. The results of this research were the total transfer time measured before and after improvements made to the process. The expected impact from this research and improvement recommendations is a better overview of the complete transfer passenger process at KEF and more efficient transfer operation at KEF. Keflavíkurflugvöllur er alþjóðaflugvöllur með þá stefnu og markmið að vilja stækka við sig og efla tengiflug í norður Atlantshafinu, milli Evrópu og Bandaríkjanna. Staðsetning flugvallarins gerir það að verkum að hægt er að bjóða upp a snöggan tengitíma sem aftur á móti getur haft slæmar afleiðingar á stundvísi brottfara frá Keflavíkurflugvelli. Í þessari rannsókn var stuðst við aðferðafræði stjórnun viðskiptaferla. Stjórnun viðskiptaferla snýr að því að auka virði ...